AXIOLOGY OF MONETARY LAW IN EXTRAORDINARY CIRCUMSTANCES: AN EXAMPLE OF EMERGENCY LAW - Dimitrijević, Marko B. (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
The subject matter of analysis in this paper are the nature, characteristics and nomotechnics of monetary law norms, both in the period of establishing classical monetary law thought and in the period of its intensive scientific popularization and academic positioning. In that context, the paper points out to the specific way of implementing monetary regulations (sources) in regular and extraordinary circumstances (periods of crisis), with special reference to the tendency of the so-called more humane approach in creating a monetary corpus, taking into account the fact that a significant number of sources of modern monetary law along with the behavior of its main actors at the national and international level (in)directly affect the citizens’ living standard. The application of the axiological, dogmatic, and comparative law method aims to point out to the a valuable factual contribution of monetary law, as an independent and positive legal discipline, to the protection of monetary rights (such as the right to a healthy and strong currency and the right to monetary stability) as a conditio sine qua non for the enjoyment of other categories of socio-economic rights and the preservation of economic stability.